Environmental Care and Cultural Invention through the SEHATI Program with the Application of Organism Response Stimulus (SOR) - Dwinanto Kurniawan; M Andri Nugroho; Catharina Siena Mira A.E; Somaya Saragih; Hendrata Wahyuesa Priambudi (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
The SEHATI program is a PT Polytama Propindo CSR program that aims to create environmental care values for elementary school students and teachers. The preparation of this program follows up on data on waste generation from several elementary schools in ring 1 of PT Polytama Propindo. Based on data collection on waste generation that has been carried out by the company, there were 898.85 kg of waste recorded in August 2019 and an increase to 967.92 kg in September. Responding to these problems, PT Polytama Propindo organized the SEHATI Program (Sekolah Hijau, Sehat, dan Bersih) as a solution to the problem of waste generation in the school area. Program implementation applies the principle of stimulus-organism response (SOR). This form of application was when PT Polytama Propindo, in collaboration with the Faculty of Agriculture at the University of Wiralodra, provided stimulus to nine elementary schools in the ring 1 area and three schools in the development ring, resulting in a response in the form of a change in behavior that became environmentally concerned.